Análisis de las protestas sociales en plataforma digitales durante la pandemia - Ramírez López, José Enrique (2020)
The present investigation takes as a target to analyze the social protests, demonstrations because of the application of Law of Humanitarian Support, approved by National Assembly on May 15, by means of the official record N ° 229, in digital platform Facebook during the pandemic. The resolutions inside this law that caused dissatisfaction in the society were: the reduction of budget of the state universities and polytechnics elimination of government-owned enterprises and reduction of salary, hence the subject of study of this case, there were the main organizations that fight for rights of these unions. For the securing of the results the methodology applied in this study was of qualitative character, across the type of diagnostic, descriptive and bibliographical investigation, supported in the skill of compilation of direct observation where the facilitating instrument of the compilation of information was the observation card. The results obtained in this study were favorable since one knew that the unions use the social network Facebook as a tool of diffusion and organization, the multimedia content stands out in this network, the strategies communications are: hashtag, videos and transmissions in alive.